CONTEMPORARY ISSUES AS GLOBAL CONCERN AND THE TEACHING OF SOCIAL STUDIES EDUCATION IN NIGERIA - Njoku, Philomena Ngozi; Busayo, Adeniji; Anyanwu, Kate Chikodi (African Journal of Social and Behavioural Sciences, 2025)
This paper examines the critical role of social studies education in addressing contemporary issues as a global concern. The paper highlights the importance of integrating relevant and significant contemporary topics into the curriculum, fostering critical thinking, global citizenship, and civic action among students. Drawing on a comprehensive set of references, the paper delves into the definition and scope of contemporary issues, presenting examples of major challenges such as climate change, inequality, and migration, and their impacts on global communities. The paper underscores the significance of technology and media literacy in enhancing social studies education, emphasizing the role of educators in utilizing multimedia resources and digital tools to engage students in understanding complex global challenges. Moreover, the integration of interdisciplinary connections between social studies and other subjects is discussed to provide students with a comprehensive understanding of contemporary issues. Addressing potential resistance and controversy in the classroom is critical to this paper, presenting strategies for creating inclusive and respectful learning environments where students can explore diverse perspectives on sensitive topics. Furthermore, the conclusion emphasizes the collective responsibility of educators, policymakers, and communities in fostering global awareness and cultivating the next generation of informed and proactive global citizens. In conclusion, this paper aims to inspire educators, policymakers, and communities to collaborate in advancing social studies education, equipping students with the necessary knowledge, skills, and perspectives to address contemporary global concerns. By nurturing empathy, critical thinking, and a commitment to positive change, we can empower students to become advocates for a more equitable, sustainable, and interconnected world.